Natural Resources and Productivity: Can Banking Development Mitigate the Curse? - Abubakr Badeeb, Ramez; Hooi, Hooi Lean (MDPI, 2017)
This paper contributes to the literature concerning the natural resource curse by exploring the role of banking development in reducing the resource curse in a natural resource-based country, Yemen. Using time series data over the period 1980–2012, we find that natural resource dependence is negatively related to productivity, and this relationship depends on the level of banking development. Increasing this level reduces the negative consequences of the natural resource curse. Therefore, policymakers should proactively encourage credit to enable the banking sector to play a more efficient intermediary role in mobilizing domestic savings and channeling them to productive investments. This will help to accumulate permanent productive wealth to enhance any diversification effort and compensate for the decline in natural resource production.